The correlation between urban sprawl and the local economy in Poland - Piotr LITYŃSKI (Urbani Izziv, 2016)

(untitled)
The literature has assessed urban sprawl as a negative phenomenon because of the costs it generates. However, various studies have examined the impact of urban sprawl based on only one parameter, such as public expenditures or fuel consumption, instead of taking a more comprehensive approach. Thus, there is a gap in research on the impact of urban sprawl on the local economy from a broader perspective. This article examines the correlation between urban sprawl and the local economy. Urban sprawl is quantified using a modified method based on sprawl indexation. GDP is used as a measure of the local economy. The analysis discussed in the article shows that greater urban sprawl is accompanied by lower GDP in municipalities. Even municipalities with a similar number of houses and varying distribution in space may differ in terms of the level of the local economy. Therefore, houses should be built more densely to achieve a higher level of the local economy. The conclusions show that losses for the local economy resulting from a chaotic spatial structure are unrelated to the distance from the city.